PENGARUH PENAMBAHAN FLOKULAN DAN KOAGULAN MENGGUNAKAN METODE JAR TEST TERHADAP KUALITAS AIR BAKU - Akda Zahrotul Wathoni; Ika Fitri Ulfindrayani; Karya Hidayat (Industry Xplore, 2020)
Water is an essential need for all living things on earth. For industrial activities, water has an important role for production and non-production activities. The use of water at a paper company in Karawang is required around 7000 m3 per day. So that the company is required to have a water treatment plant to meet the needs of production and non-production water. The function of the raw water treatment plant (Raw water Treatment) in the company aims to get good water quality from its water source, namely Citarum river water. So it is necessary to analyze the condition of the water first by means of the Jar test. With the Jar test, the optimum dose can be determined in the addition of coagulant and flocculant solutions. In addition, the jar test with the addition of flocculants and coagulants can also reduce the pH and turibidity of raw water. From the results of statistical tests using a paired sample test, pH and Turbidity levels have a significant change with a value of (Sig.) < 0.05, so H0 is rejected. The method of adding flocculants and coagulants with the Jar Test method can reduce pH levels of 10% and Turbidity of 95%.